Does Temporary Migration Have to Be Permanent? - Amin, Mohammad; Mattoo, Aaditya (World Bank, Washington, DC, 2012)
The choice between temporary and permanent migration is today central to the design of migration policies. The authors draw a distinction between the two types of migration on the basis of the associated social cost and the dynamics of learning by migrants. They find that unilateral migration policies are globally inefficient because they lead to too much permanent migration and too little temporary and overall migration. Existing international agreements on labor mobility, such as the World Trade Organization's General Agreement on Trade in Services, have failed to do better because they seek primarily to induce host countries to make commitments to allow entry. Instead, Pareto gains and more liberal migration could be achieved through multilateral agreements that enable host countries to commit to repatriation.